Fiscal Federalism in a Monetary Union: The Cooperation Pitfall - Hubert Kempf (Center for Economic Studies and ifo Institute (CESifo), 2017)
Fiscal federalism may not be a panacea in a monetary union if it does not address the non-cooperative behaviour between fiscal policymakers. To prove this, we assess the relative merits of a fiscal federalism scheme in a monetary union and intergovernmental fiscal cooperation without such a federal authority. Using a standard macroeconomic model commonly used for policy analysis we show that it is impossible to conclude that one solution is always preferable to the other. The benefits from an extra instrument and a policymaker with union-wide objectives may not compensate the adding of a non-cooperative player to the policy game. This result is sustained when an active monetary policy is introduced in the model or when shocks affect the functioning of the economy. The welfare ranking of these two options depends on the cross-border spillover effects, the objectives of policymakers and the variances of shocks.
Keywords: E62; E63; F45; 330; monetary union; fiscal federation; cooperation; policymix